2022
DOI: 10.3390/agriculture12091428
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Organic and Chemical Nitrogen Fertilizers on the Crop Yield and Fertilizer Use Efficiency of Soybean–Maize Intercropping Systems

Abstract: The effect of the mixture (1:1) of chemical and organic nitrogen (N) fertilizer on crop yield quality and N fertilizer use efficiency remains elusive. A nitrogen field experiment was conducted in the growing seasons of 2020 and 2021 to investigate the effects of the mixture of chemical and organic N fertilizer on the crop yield, crop quality and nitrogen fertilizer use efficiency in a maize–soybean intercropping system in China. Four treatments applied at 150 kg N ha−1 were used: no nitrogen fertilizer (CK), c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The released nutrient rate may not coordinate with soybean protein formation but coordinate with fat formation (Liu et al., 2021). The other possible explanation for the result is that soybean protein and oil content may be mainly determined by the gene ( Lin et al., 2022 ). In addition, soil microorganisms and environment also have an impact on crop quality ( Studnicki et al., 2016 ; Kundel et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The released nutrient rate may not coordinate with soybean protein formation but coordinate with fat formation (Liu et al., 2021). The other possible explanation for the result is that soybean protein and oil content may be mainly determined by the gene ( Lin et al., 2022 ). In addition, soil microorganisms and environment also have an impact on crop quality ( Studnicki et al., 2016 ; Kundel et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Lin and co-authors found that the protein concentration was increased with organic and chemical fertilizers, while the oil contents were decreased with the same treatment. These authors also noted that the combined use of chemicals and organic fertilizers resulted in a reduction in their starch contents, and there was no significant impact of this combination on the nitrogen harvest index (ratio of N accumulated in grain to N accumulated in grain plus straw) [82]. The use of organic fertilizers substantially increased the seed quality parameters and nitrogen use efficiency (NUE) of plants [83,84].…”
Section: Effect Of Organic Fertilizers On Quality Of Cropsmentioning
confidence: 96%
“…However, some authors found no advantage of chemical and organic fertilizing in increasing nutrient uptake and the NUE [119]. Other authors also found that the combined use of chemicals and organic fertilizers increased the N partial productivity (NPP), N agronomic efficiency (NAE), fertilizer use efficiency and N fertilizer recovery rate (NFRR) in maize and soybean [82,120]. The slow and gradual release of nutrients and the increase in organic matter with organic fertilizers is linked with an improved NUE [121][122][123].…”
Section: Effect Of Organic Fertilizers On Soil Nutrient Status and Nu...mentioning
confidence: 99%
“…For the farmer, the interest is twofold: (i) a reduction of mineral nitrogen inputs and thus of production costs, and (ii) a less polluting production since the mineral nitrogen usually used in conventional agriculture is highly leachable. The competitiveness of the cereal on nitrogen uptake ends up capturing the residual mineral nitrogen of the previous crop, while the symbiotic fixation of atmospheric nitrogen by the legume provides a resource for its own need and completes the missing needs of the complementary plant [21][22][23][24].…”
Section: Ecological and Economic Advantages Of The Pea And Wheat Inte...mentioning
confidence: 99%